Pro NuGet - Balliauw, Maarten; Decoster, Xavier; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
Pro NuGet offers you a solid architectural understanding of how to manage software dependencies using NuGet, an open-source package management tool for the .NET Framework. Providing practical guidance through a multitude of examples and more advanced scenarios, this book shows you how to unleash all the power that NuGet offers. It will help you to streamline your day to day development and even make it more fun to write code. Authors Maarten Balliauw and Xavier Decoster have been working with NuGet since it was first released, contributing many ideas and practical solutions to the community over that time. In this book they demonstrate both the core concepts and the more advanced thinking needed to use NuGet effectively.
Keywords: Computer science; Computer Science; Computer Science, general